Media and Information Literacy Among Children on Three Continents: Insights into the Measurement and Mediation of Well-being. - Livingstone, Sonia; Burton, Patrick; Cabello, Patricio; Helsper, Ellen; Kanchev, Petar; Kardefelt-Winther, Daniel; Perović, Jelena; Stoilova, Mariya; Yu, Ssu-Han (Corporación Universitaria Minuto de Dios - UNIMINUTO, 2021)
In understanding and promoting positive outcomes for children’s Internet use, media and information literacies (MILs) play a crucial mediating role, by enabling opportunities for learning, creating, expressing oneself and participating and by facilitating coping and building resilience. This chapter explains the approach adopted by Global Kids Online (GKO), a multinational research partnership, seeking to generate robust evidence that can inform policy and practice regarding children’s internet use in diverse cities and countries internationally. The chapter presents the rationale for GKO’s multidimensional approach to MIL and issues of measurement, social desirability, and cross-national comparison. Additionally, it presents recent findings showing cross-national similarities in higher operational levels than creative skills and differences between higher and lower income countries; it is noteworthy that gender differences in children’s digital skills are found to be minimal. Having shown that the GKO quantitative research toolkit successfully operationalizes the range of MILs also addressed by comparable international frameworks, we recommend the approach to future researchers, concluding with an evidence that GKO’s research results are now being used to inform national policy and practice regarding children’s learning in a digital age.
Capítulo 5 - MIL Cities and MIL Citizens: Informed, Engaged, Empowered by Media and Information Literacy (MIL).
Keywords: Global Kids Online; Digital skills measurement; Policy implications